The emergence of biological invasions on food chains: a DPSIR analysis. Issue 3 (10th November 2020) - Faraudello, Alessandra; Gualtieri, Donato; Szeles, Zsuzsanna
Abstract : Purpose: The purpose of this paper is to illustrate the emergence of a biological invasion and to explain the potential economic and social consequences on food chains. Straddling between ecology, social sciences, resource management and economics, invasion science is aimed at detecting, understanding and mitigating the impact of biological invasions on receiving ecosystems, including food ecosystems. Design/methodology/approach: After a theoretical investigation about the main notions relevant for the invasion science, the authors practically review the kind of impacts deriving from biological invasions, mainly under economic, human health, ecosystem and biodiversity criteria. Findings: The authors apply the DPSIR (Driving forces–pressure-state-impact-response) framework, originally developed in the context of European Environment Agency in this different context in order to assess the social, economic and environmental impacts of Invasive Alien Species (IAS). Responding to this emerging phenomenon, the European Union issues the EU regulation 1143/2014 which is the first strong act on invasive alien species. Originality/value: Implications – Food chains are complex systems that have multiple interdependencies both endogenously and exogenously, such as food production, food transportation, food logistics, food distribution, and so forth. However, it is rarely conceived the impact of invasion systems on the dynamics of food chains, although food sustainability is in turn impacted by how effectively and efficiently the various interdependencies have been designed or are working.